Injury History in the Collegiate Equestrian Athlete: Part II: Head, Upper and Lower Extremities - Michael L. Pilato; Timothy Henry; Drussila Malavase (Bowling Green State University, 2017)
Purpose: Equestrian sports are known to have a high risk and rate of injury. While there is injury data available on acute injuries in the equestrian population, it is of a general nature. Within that data appears to be a lack of information on the collegiate equestrian athlete. Thus, the purpose of the current study and this analysis is to describe the incidence of upper and lower extremity injuries and head injuries, sans concussion, in intercollegiate equestrian athlete. Method: A survey was developed with input from each author and implemented in Mach forms. It was sent to 43 equestrian coaches in the Eastern United States who passed it on to their athletes. We estimated 753 athletes would have access to the survey and had a total of 73 respondents. Descriptive statistics were calculated for total number of injuries for each injury category. Results: Detailed injury information on the upper and lower extremity and head is found in tables 1-10. The upper and lower extremity and head accounted for 15.97, 60.35 and 4.33 percent respectively of the injuries in this group of athletes.Conclusions and Recommendations:The current study is amongst the first, if not the first, to report specifically on injury patterns and frequency in US collegiate equestrian athletes. The data indicate that there is an extremely high incidence of injury in the collegiate equestrian population. The lower extremity is particularly susceptible to injury in the equestrian athletes. The lack of data available in a sport, which can be classified as collision and has the potential for significant, long-standing disability from an early age due to interaction with the horse, is troubling. Significantly more sport specific research is needed to improve the health and safety of these athletes.